THE INFLUENCE OF SKILLS, WORK STRESS, COMMUNICATION, AND MOTIVATION OF EMPLOYEE PERFORMANCE TO PT. MERAK JAYA BETON IN DISTRICTS MOJOKERTO - novita, mega darmi; mahendra, angga martha; soesanto, soesanto (Ekspektra : Jurnal Bisnis dan Manajemen, 2020)
This study aims to analyze the effect of skills, work stress, communication, and motivation on the performance of the employees of PT. Merak Jaya Beton Mojokerto. The total sample of the study amounted to 55 people. The variables used are skills, work stress, communication, and motivation as independent variables and employee performance as the dependent variable. Data collection was carried out by questionnaire and then analyzed using multiple linear regression analysis methods. Hypothesis testing used is the simultaneous significance test (F-test) and partial significance test (T-test). The results of the F test of this study indicate that the variable of skills (X1), work stress (X2), communication (X3), and motivation (X4) simultaneously influence employee performance. While the T test shows the variable of skills (X1), work stress (X2), communication (X3) have no partial effect on employee performance, while the motivation variable (X4) has a partial effect on employee performance.